2017
DOI: 10.4236/psych.2017.814156
|View full text |Cite
|
Sign up to set email alerts
|

When Kids Hurt Other Kids: Bullying in Philippine Schools

Abstract: This research looked into prevalence rate of bullying victimization and perpetration as well as teachers' response to bullying incidence in the Philippines. A total of 340 sixth graders from five different schools in Western Visayas participated in the study. Slightly more than half (54.1%) of the sample were boys and 45.9% were girls. Descriptive statistics were used to analyze data gathered from the survey. Children's self-reports revealed that prevalence rate for victimization was 40.6% and that for perpetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 38 publications
3
14
1
2
Order By: Relevance
“…The cases of victimization were also documented in African countries (Kubwalo, Muula, Siziya, Paupulati, & Rudatsikira, 2013;Owusu, Hart, Oliver, & Kang, 2011) with the prevalence rate of more than 40%. In Pakistan, the rate was lower (17.9%) compared to the study conducted by Sanapo (2017) in Philippine where the frequency of victimization reached 40.6%. The data was uniquely different in Hongkong, Taiwan, Macao (Mok, Wang, jutenfren, Leung, & Chen, 2014) and Thailand (Sittichai & Smith, 2015), in which less than 10% of the students reported having experienced bullying.…”
Section: A Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The cases of victimization were also documented in African countries (Kubwalo, Muula, Siziya, Paupulati, & Rudatsikira, 2013;Owusu, Hart, Oliver, & Kang, 2011) with the prevalence rate of more than 40%. In Pakistan, the rate was lower (17.9%) compared to the study conducted by Sanapo (2017) in Philippine where the frequency of victimization reached 40.6%. The data was uniquely different in Hongkong, Taiwan, Macao (Mok, Wang, jutenfren, Leung, & Chen, 2014) and Thailand (Sittichai & Smith, 2015), in which less than 10% of the students reported having experienced bullying.…”
Section: A Introductioncontrasting
confidence: 56%
“…A study by Bond, Wolfe, Tollit, Butler, and Patton (2007) revealed that students in Australia had more experiences of being hurt and threatened physically, teased, called names, and spread rumors. In Asia-Pacific and South America countries, more students had been called by unpleasant nicknames, being laughed and cursed (Jolliffe & Farrington 2011;Lai, Ye, & Chang, 2008;Sanapo 2017;Silva, Pereira, Mendonca, Nunes, & de Oliveira, 2013;). Results from the studies indicated that verbal bullying was found to be the most common category reported by students (Jolliffe & Farrington 2011;Marsh et al, 2010).…”
Section: Bullying Victimization Gender and Grade Levelmentioning
confidence: 99%
“…This can also be inferred that students did not refer verbal bullying and interests and skills due to the movies they've watched and the environment they belong. According to Sanapo (2017), the study also revealed that verbal bullying and victimization was the common from experienced by the children. The table above shows that the computed value of cyber bullying vs.…”
Section: Level Of Student's Attitudementioning
confidence: 92%
“…According to Gini, Pozzoli, Borgi and Franzoni (2008), bullying is a negative behavior and becomes a public health concern that receives attention from the media and policymakers (Waasdrop, Pas, Zablotsky and Bradshaw, 2017) which requires deeper reflection on the cultured diversity (Koifman and Botelho da Costa, 2016). bullying is also a problem in the peer relations by the imbalance power between the parties (De Oliveira, Silva, Braga, Romualdo, Caravita and Silva, 2016) which is associated with physical, mental, and social detriments (Dake, Price, and Telljohan, 2003) and is usually form of derogatory remarks or insults hurled at the target (Sanapo, 2017).…”
Section: Identify Research and Collect Datamentioning
confidence: 99%
See 1 more Smart Citation